(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Morphological analyser & generator (MAG) plays an important Natural LanguageProcessing application and are compulsory apparatuses in Machine Translation. In the work proposed, MAG for Kannada language were created utilizing rule based just as factual methodology by fusing morphological data and characteristics of the language. The classification of words into various paradigms dependent on their inflections and orthographic changes, structuring the morphological framework, rule and corpus creations are the primary difficulties in the advancement of generator.The MAG tool is constructed for Kannada texts using machine learning strategies and produced theoutcomes using numerouskinds of eight input data sets. The validation of GUIs and processing of tool is carried out and the snapshots along with the tabulated and graphical performance analysis are published in the work.